RF-MBE and MOVPE InxGa1-xN films over the entire composition range: A study on growth method dependence. (April 2020) - Bhuiyan, Ashraful G.; Islam, Md. Sherajul; Hironaga, Daizo; Hashimoto, Akihiro
Abstract: This paper reports the influence of different growth methods on the Inx Ga1-x N ternary alloys over the entire composition range. We have successfully fabricated the single crystalline Inx Ga1-x N alloys without phase separation and metal indium (In) inclusion over the entire In composition region by the RF-MBE and MOVPE methods. The fluctuation of the c-axis is found smaller in the RF-MBE Inx Ga1-x N alloys while the fluctuation of a-axis is found smaller in the MOVPE Inx Ga1-x N alloys. We show that the Raman inactive B1 (High) mode has appeared in addition with the E2 (High) and A1 (LO) modes in this ternary alloy. The behavior of E2 (High) and B1 (High) modes of the Inx Ga1-x N alloys greatly depends on the composition and growth method. It is also found that the growth method dependence behavior of the FWHM of E2 (High) mode is similar to the a-axis fluctuation behavior in the XRC analysis. Our results spectacle that the local lattice distortion in the MOVPE grown Inx Ga1-x N alloys in the intermediate In composition region is very large compared with the RF-MBE samples. These findings are very important to better understand the fabrication of high-quality Inx Ga1-x N alloys aimed at the further development of InGaN-based high-performance optoelectronics and solar cells. Highlights: We report a comprehensive insight of various growth methods dependence of the InGaN. We show that Raman inactive B1 (High) mode is appeared in InGaN ternary alloy. The lattice distortion in intermediate In range is larger in MOVPE InGaN than MBE sample.